Clinical neuropsychology : a practical guide to assessment and management for clinicians - Goldstein, Laura H. (Laura Hilary), 1960-; McNeil, Jane E. (Wiley, 2004)
Clinical Neuropsychology A Practical Guide to Assessment and Management for Clinicians shows how knowledge of neuropsychological applications is relevant and useful to a wide range of clinicians. It provides a link between recent advances in neuroimaging, neurophysiology and neuroanatomy and how these discoveries may best be used by clinicians. Anyone working with clients whose cognitive functioning shows some change and who needs to assess and make recommendations about rehabilitation and management will find this book essential reading.: Practical focus on what is important for clinicians in.